2020
DOI: 10.1167/iovs.61.8.41
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 Mediates Fibrosis in Corneal Endothelial Mesenchymal Transition Through SP1 and SP3

Abstract: PURPOSE. ZEB1 is induced during endothelial-mesenchymal transition (EnMT) in the cornea. Induction of SP1 and SP3 by ZEB1 along with identification of putative SP1 and SP3 binding sites in promoters of EnMT-associated gene lead us to investigate their roles in retrocorneal membrane formation in the corneal endothelium. METHODS. Expressions of SP1, SP3, and EnMT associated genes were analyzed by immunoblotting and semiquantitative reverse transcription polymerase chain reaction. Accell SMARTpool siRNAs targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
0
19
0
1
Order By: Relevance
“…In adults, ZEB1 plays an important role in stem cell homeostasis, immune response, and angiogenesis [ 21 , 64 , 65 ]. However, abnormal activation may cause cellular transformation like EMT leading to tumorigenesis and fibrosis [ 8 , 56 ]. Therefore, targeting ZEB1 is a potential avenue to generate therapeutics for treatments of various ZEB1-related disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In adults, ZEB1 plays an important role in stem cell homeostasis, immune response, and angiogenesis [ 21 , 64 , 65 ]. However, abnormal activation may cause cellular transformation like EMT leading to tumorigenesis and fibrosis [ 8 , 56 ]. Therefore, targeting ZEB1 is a potential avenue to generate therapeutics for treatments of various ZEB1-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of Fgf2 in mouse corneal endothelial cells by siRNA inhibited the injury-dependent expression of Fgf2, Snai1, Zeb1, and Cdh1, indicating that corneal EnMT is under the control of the Fgf2-activated EMT factor Zeb1 [ 55 ]. Transient FGF2 stimulation could increase the expression of SP1 and SP3 in human corneal endothelial cells whereas knockdown of ZEB1 by siRNA only reduced the expression of the FGF2-induced SP1 mRNA and protein, but not SP3 [ 56 ]. The expression of the FGF2-induced EnMT genes such as FN1, VIM and COLI was reduced by siRNA knockdown of SP1 and SP3.…”
Section: Zeb1 and Corneal Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic analysis may provide insights into the ideal micro-environmental milieu for CEC behaviour and throw up clues for further refining CEC culture or in-vivo regeneration [28,29]. ZEB1 has been implicated in EnMT via induction of SP1 and SP3, and may be a target for therapies to prevent EnMT during CEC proliferation [30]. Recently, it was reported that microRNA-30c-1-transfected CECs showed increased resistance to TGF-b1-induced senescence and had better cell viability and proliferation [31].…”
Section: Corneal Endothelial Cell Physiologymentioning
confidence: 99%
“…Die Membrandicke variierte zwischen 2 μm und 520 μm [1]. Als Ursprung für die fibröse RCM, die erstmals 1901 durch den österreichischen Augenarzt Professor Ernst Fuchs beschrieben wurde [2,6], wurden eine stromale Zellinvasion durch eine nicht vollständige Spender-Empfänger-Adhärenz [10] und/oder endothelial-mesenchymale Transformation vermutet [1,3,5,6]. In einer aktuellen Studie von Naranjo et al [7] waren die immunhistologischen Marker für die endothelial-mesenchymale Transformation positiv, was die wichtige Rolle dieses Mechanismus für die Pathogenese der fibrösen RCM unterstreicht.…”
Section: Infoboxunclassified